Sistem Penghidupan Petani di Kawasan Konflik Agraria (Kasus: Desa Setrojenar, Kecamatan Buluspesantren, Kabupaten Kebumen) - Indri Mariska; Heru Purwandari (Jurnal Sosiologi Nusantara, 2025)
Agrarian conflict in Setrojenar involves various actors; military, farmers, and governments, as they have different interests of land. These varied interests cause significant problems regarding rights and access to utilizing resources among those actors. The military utilizes land for training purposes. On the other hand, farmers cultivate the land for agriculture.  This article scrutinized how farmers’ involvement in agrarian conflicts allows them to experience conditions of uncertainty in their efforts to survive, especially when the level of conflict increases. Farmer households must be able to adapt and implement survival strategies with the livelihood assets/capital (natural physical, capital, human, and financial capital, and social capital) they have. This study aims to analyze the correlation between the level of agrarian conflict and farmer households’ strategy and livelihood assets. This study applied a quantitative method supported by a qualitative method. Quantitative data were obtained using a research questionnaire and processed using Spearman’s rank, while qualitative data were collected by conducting interviews. The results of the study show that the level of agrarian conflict significantly correlates with the livelihood assets and strategies of farmer households. The uncertainty experienced by farming households is regarding the agricultural activities they carry out when the intensity of the conflict increases or when the Indonesian Army (Tentara Angkatan Darat) training activities take place.